2010
DOI: 10.1016/j.jacc.2010.06.044
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal and Circumferential Strain Rate, Left Ventricular Remodeling, and Prognosis After Myocardial Infarction

Abstract: Both longitudinal and circumferential SRs were independent predictors of outcomes after MI, whereas only circumferential SRs was predictive of remodeling, suggesting that preserved circumferential function might serve to restrain ventricular enlargement after MI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
199
4
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 277 publications
(216 citation statements)
references
References 41 publications
8
199
4
5
Order By: Relevance
“…Thus, echocardiographic longitudinal strain is considered the most sensitive measure of endocardial as well as subendocardial function, which is the myocardial layer of the ventricle considered most susceptible to stressors such as ischemia, mechanical stretch, and afterload resistance. Although previous studies have also demonstrated abnormalities in circumferential and radial strain in the setting of overt and severe ischemic heart disease,4, 38 longitudinal strain may represent a particularly sensitive marker of the cardiac dysfunction that occurs from early and chronic exposure to risk factors that specifically predispose to the future development of CHD. Indeed, we observed no significant relation of strain measured in other planes with incident CHD in our large ambulatory cohort, comprising individuals who were generally healthy without any prevalent CVD at baseline.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Thus, echocardiographic longitudinal strain is considered the most sensitive measure of endocardial as well as subendocardial function, which is the myocardial layer of the ventricle considered most susceptible to stressors such as ischemia, mechanical stretch, and afterload resistance. Although previous studies have also demonstrated abnormalities in circumferential and radial strain in the setting of overt and severe ischemic heart disease,4, 38 longitudinal strain may represent a particularly sensitive marker of the cardiac dysfunction that occurs from early and chronic exposure to risk factors that specifically predispose to the future development of CHD. Indeed, we observed no significant relation of strain measured in other planes with incident CHD in our large ambulatory cohort, comprising individuals who were generally healthy without any prevalent CVD at baseline.…”
Section: Discussionmentioning
confidence: 94%
“…Given the need for more‐sensitive measures of LV performance, advances in image analysis have led to noninvasive methods for assessing cardiac mechanical function in multiple planes 2, 3. Numerous studies have now demonstrated that speckle tracking analyses of LV strain (ie, myocardial tissue deformation) applied to routine echocardiography offer significant incremental prognostic information over EF in patients with known cardiovascular disease (CVD) 4, 5, 6, 7, 8, 9. However, there are few studies of LV strain and outcomes in community‐dwelling individuals free of overt CVD 10, 11.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical and animal studies have shown that increased wall stress induces changes in proteins, contractile element synthesis and gene expression that support the remodeling process 3,4,5 . Increased wall stress has also been shown to be an independent predictor of subsequent LV remodeling 6,7 .…”
Section: Introductionmentioning
confidence: 99%
“…Understanding ethnic differences and similarities is important for understanding cardiovascular disease experiences among Indigenous populations. Longitudinal strain is a correlate of LV contractility and indicates regional myocardial dysfunction and longitudinal and circumferential strains are prognostic of cardiovascular events and survival [4345]. Further, elastance and arterial–ventricular coupling provide insight into the interaction between the arterial system and the LV, evaluating stroke work and energetic efficiency and providing indications of atherosclerotic heart disease [46].…”
Section: Discussionmentioning
confidence: 99%